Single-handed multi-modal interface for robotic application in an industrial environment - Pang, Hong Yun (2017)
The proliferation of artificial intelligence technologies and computerization has given rise to an era of automation. Human and robot interaction is now inevitable as robotic systems has become one of the pillars of industrial growth. From primordial tools like spears and stones in the past to the intricate robots used today, the relationship between man and tools is ever-changing. The robots, coupled with multiple customizations, must satisfy the needs of their respective industries to allow operators to utilise the robots to their fullest potential. As such, human-robot interaction should keep up with the roles of the robots as they evolve to suit industrial needs. Today, the human-robot systems are shifting their focus to the collaboration between the two, by using a more interactive human-robot interface to facilitate the system. However, the current keyboards and mouse interface is inadequate in meeting the requirements of the autonomous and semi-autonomous robots employed in the industrial applications. These industries applications demand swift and effective communication and exchange of data between human and robot. Therefore, the purpose of this project will be to improve human-robot systems through using augmented reality technology which is on the rise. This project employs the augmented reality technology to enhance the collaborative nature (2-way interaction) of human-robot systems by improving its system's interface, and aims to aid the control of robotic systems via a single-handed multi-modal interface for automatic robot taping. The taping is done autonomously by an agile robotic system with intuitive control. A unique framework was implemented for a collaborative human-robot interaction, incorporating a user-centered design to enhance feedback to users which improves robot usability.